An ANALYSIS OF DISFLUENCIES FOR DESCRIBING PHENOMENA IN SPONTANEOUS SPEECH AS A DESCRIBING OF SIMPLE RESEARCH FOR QUALITATIVE METHOD - Feri Ferri Susanto (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
This research is motivated by a phenomenon that is often found when students speak English. This phenomenon can be found in spontaneous speech, the researcher wants to know and describe the non-fluency in spontaneous speech used by fourth semester English students at UIN FAS Bengkulu. The form of research is a qualitative descriptive. It has the spontaneous speech object of the fourth semester English students of UIN FAS Bengkulu. Researchers collected data in several steps; first, he gave the topic to the students, the second the students were instructed to speak the given topic, the next time was 5 minutes, the last was recording the students speaking. After that, the researcher analyzed it in several steps; First, he transcribed the students' speech, classified the types of non-fluency, coded the non-fluency, analyzed all the data, interpreted and concluded. The results of this study indicate that there are still many students who make mistakes in speaking spontaneously. Students make more mistakes in repairing, especially in repetition. Paying attention to vocabulary changes in speech is very important to tell them how to speak well. The researcher concludes that in spontaneous speech that the four types of non-fluency (unfilled pause, filled pause, ritual speech unit, and correction) proposed by the fourth semester English students of UIN FAS Bengkulu by sentences in spontaneous speech. 1. There are 28 non-fluency in the unfilled pause, 2. There are 46 non-fluency in the filled pause, 3. There are 2 non-fluency in the ritual speech unit, 4. There are 57 non-fluency in the improvement. The researcher suggested that the students improve their speaking skills to make the right form of their speaking